2020
DOI: 10.3389/fmicb.2020.591287
|View full text |Cite
|
Sign up to set email alerts
|

Genome- and Proteome-Wide Analysis of Lysine Acetylation in Vibrio vulnificus Vv180806 Reveals Its Regulatory Roles in Virulence and Antibiotic Resistance

Abstract: Infection with Vibrio vulnificus is notorious for its atypical clinical manifestations and irreversible disease progression. Lysine acetylation is a conserved post-translational modification (PTM) that plays a critical regulatory role in diverse cellular processes. However, little is known about the role of lysine acetylation on the pathogenesis of V. vulnificus. Here, we report the complete genome sequence and a global profile for protein lysine acetylation of V. vulnificus Vv180806, a highly cefoxitin resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 69 publications
2
15
0
Order By: Relevance
“…This has also been discovered in diverse organisms, which may make clear that acetylation plays a jointly regulatory role in central metabolic enzymes ( Choudhary et al, 2014 ). Furthermore, previous research reported that large-scale ribosome-related proteins were acetylated, such as in A. hydrophila , V. vulnificus , and S. pneumoniae ; our results also indicated the proteins involved in ribosome were more abundant through KEGG enrichment analysis ( Liu et al, 2018 ; Sun et al, 2019 ; Pang et al, 2020 ).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…This has also been discovered in diverse organisms, which may make clear that acetylation plays a jointly regulatory role in central metabolic enzymes ( Choudhary et al, 2014 ). Furthermore, previous research reported that large-scale ribosome-related proteins were acetylated, such as in A. hydrophila , V. vulnificus , and S. pneumoniae ; our results also indicated the proteins involved in ribosome were more abundant through KEGG enrichment analysis ( Liu et al, 2018 ; Sun et al, 2019 ; Pang et al, 2020 ).…”
Section: Resultssupporting
confidence: 73%
“…MF analysis revealed that acetylated proteins were outstandingly enriched in binding, heterocyclic compound binding, organic cyclic compound binding, and ion binding ( Figure 3A ). Consistent with previous research, the identified acetylproteins mainly enrich for metabolism processes, location of the cell, and binding function, which are especially similar to Vibrio spp., such as Vibrio cholerae V52, Vibrio alginolyticus , Vibrio parahemolyticus , and Vibrio vulnificus Vv180806 ( Pan et al, 2014 ; Carsten et al, 2017 ; Pang et al, 2019 ; Pang et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, none of these predictions have been experimentally confirmed; therefore, the physiologic significance of these observations remains unclear. The acetylomes of other pathogenic Vibrio species have also been characterized, including V. vulnificus ( 37 ), V. parahaemolyticus ( 38 ), and V. alginolyticus ( 39 ), but investigation of potential virulence factors was not extensively explored.…”
Section: Acetylome Analysis In Pathogenic Bacteriamentioning
confidence: 99%